Image quality optimization using a narrow vertical detector dental cone-beam CT - Brasil, Danieli Moura (Dentomaxillofac Radiol, 2019)
OBJECTIVES: To determine the optimized kV setting for a narrow detector cone-beam CT (CBCT) unit. METHODS: Clinical (CL) and quantitative (QUANT) evaluations of image quality were performed using an anthropomorphic phantom. Technical (TECH) evaluation was performed with a polymethyl methacrylate phantom. Images were obtained using a PaX-i3D Green CBCT (Vatech, Hwaseong, Korea) device, with a large 21 × 19 and a medium 12 × 9 cm field of view (FOV), and high-dose (HD–ranging from 85 to 110 kV) and low-dose (LD–ranging from 75 to 95 kV) protocols, totaling four groups (21 × 19 cm HD, 21 × 19 cm LD, 12 × 9 cm HD, 12 × 9 cm LD). The radiation dose within each group was fixed by adapting the mA according to a predetermined dose-area product. For CL evaluation, three observers assessed images based on overall quality, sharpness, contrast, artefacts, and noise. For QUANT evaluation, mean gray value shift, % increase of standard deviation (SD), % of beam hardening and contrast-to-noise ratio (CNR) were calculated. For TECH evaluation, segmentation accuracy, CNR, metal artefact SD, metal object area, and sharpness were measured. Representative parameters were chosen for CL, QUANT, and TECH evaluations to determine the optimal kV based on biplot graphs. kV values of the same protocol were compared by the bootstrapping approach. The ones that had statistical differences with the best kV were considered as worse quality. RESULTS: Overall, kV values within the same group showed similar quality (p > 0.05), except for 110 kV in 21 × 19 cm HD and 85 kV in 12 × 9 cm HD of CL score; also 85, 90 kV in 21 × 19 cm HD and 75, 80 kV in 21 × 19 cm LD of QUANT score which were worse (p < 0.05). CONCLUSION: At a constant dose, low and high kV protocols yield acceptable image quality for a narrow-detector CBCT unit.